METHODOLOGICAL FEATURES OF DEVELOPING THE TECHNIQUE OF DRIBBLING, PASSING, AND SHOOTING IN FOOTBALL (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The development of technical skills is a fundamental component of football training and plays a decisive role in the effectiveness of players during competitive matches. Among the most essential technical elements of football are dribbling, passing, and shooting, which determine the quality of ball control, team interaction, and goal-scoring efficiency. Modern football requires players not only to possess physical endurance and tactical awareness but also to demonstrate highly refined technical abilities that allow them to perform under conditions of time pressure, defensive resistance, and dynamic game situations. Therefore, the methodological organization of training aimed at improving these technical elements is an important task in sports pedagogy and coaching practice. This study examines the methodological features of developing the technique of dribbling, passing, and shooting in football within the framework of pedagogical training in higher educational institutions specializing in sports. Particular attention is given to the integration of scientifically grounded training methods, progressive exercise systems, and pedagogical principles that support the gradual development of technical proficiency. The research highlights the importance of differentiated instruction, repetitive practice, situational exercises, and game-based training models that simulate real match conditions. The study also analyzes the pedagogical conditions necessary for effective technical development, including systematic training organization, gradual complication of exercises, and the integration of individual and group practice formats. Emphasis is placed on the role of coaching guidance, feedback mechanisms, and performance evaluation in shaping stable motor skills. The findings demonstrate that the consistent application of scientifically based methodological approaches significantly improves the quality of technical actions performed by football players.Overall, the research contributes to the methodological understanding of football training by identifying effective strategies for developing key technical skills among students in sports-oriented pedagogical institutions. The results may be used in educational programs, coaching practice, and methodological recommendations for improving the technical preparation of football players.